Comparative analysis of the current payment system for hospital services in Serbia and projected payments under diagnostic related groups system in urology - Babić, Uroš Momčilo; Soldatović, Ivan; Vuković, Dejana; Šantrić Milićević, Milena; Stjepanović, Mihailo; Kojić, Dejan; Argirović, Aleksandar; Vukotić, Vinka (Vojnosanitetski pregled, 2015)
Background/Aim. Global budget per calendar year is a traditional method of funding hospitals in Serbia. Diagnose related groups (DGR) is a method of hospital payment based on classification of patients into groups with clinically similar problems and similar utilization of hospital resources. The aim of this study was to compare current methods of hospital services payment with the projected costs by DRG payment method in urology. Methods. The data were obtained from the information system used in the Clinical Hospital Center “Dr. Dragiša Mišović” – Dedinje in Belgrade, Serbia. The implemented hospital information system was the main criterion for selection of healthcare institutions. The study included 994 randomly selected patients treated surgically and conservatively in 2012. Results. Average costs under the current payment method were slightly higher than those projected by DRG, however, the variability was twice as high (54,111 ± 69,789 compared to 53,434 ± 32,509, p
Keywords: hospitals; financial management; urology; serbia